2006
DOI: 10.5194/acpd-6-12549-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dangerous human-made interference with climate: a GISS modelE study

Abstract: Abstract. We investigate the issue of "dangerous human-made interference with climate" using simulations with GISS modelE driven by measured or estimated forcings for 1880–2003 and extended to 2100 for IPCC greenhouse gas scenarios as well as the "alternative" scenario of Hansen and Sato (2004). Identification of "dangerous" effects is partly subjective, but we find evidence that added global warming of more than 1°C above the level in 2000 has effects that may be highly disruptive. The alternative scenario, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 113 publications
4
90
0
Order By: Relevance
“…By 2070-2099, in all of the projections, temperature increases were sufficient to nearly eliminate seasonal mean temperatures in the lower third of the distribution and sharply reduce those in the middle third. Such climate changes would be, in the words of Hansen et al 2007, "climate changes outside of the range of local experience." A noteworthy feature in the temperature projections is that the warming through the twenty-first Century does not level off, especially in projections using the medium and high greenhouse gas emission scenarios, implying that California's climate would continue to warm in (at least) the subsequent decades of the twenty-second century.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…By 2070-2099, in all of the projections, temperature increases were sufficient to nearly eliminate seasonal mean temperatures in the lower third of the distribution and sharply reduce those in the middle third. Such climate changes would be, in the words of Hansen et al 2007, "climate changes outside of the range of local experience." A noteworthy feature in the temperature projections is that the warming through the twenty-first Century does not level off, especially in projections using the medium and high greenhouse gas emission scenarios, implying that California's climate would continue to warm in (at least) the subsequent decades of the twenty-second century.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…The Alternative scenario ends at a CO 2 concentration of 475 ppm in 2100. In Hansen et al (2007) the GISS modelE coupled climate model was forced with this scenario, and it was found that the Alternative scenario kept the future global warming below 1 • C with respect to the end of the twentieth century for a climate sensitivity of about 3 • C or less for doubled CO 2 . May (2008) used a somewhat different approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, even use of multiple pdf's tends to keep the focus on planning for the most likely outcomes at the expense of the extremes (unless the pdf's are dissimilar). This can be dangerous when the stakes associated with the extremes (the upper end of climate sensitivity estimates in this case) are so high (Schneider 1997;Kasting 1998;Hansen 2005;Hansen et al 2007). We need to supplement pdf's as a tool for communicating climate sensitivity with another method that is capable of highlighting extremes.…”
Section: Discussionmentioning
confidence: 95%